2015
DOI: 10.1007/s13665-015-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in interstitial lung disease: moving towards composite indexes and multimarkers?

Abstract: Interstitial lung disease (ILD) covers a large spectrum of lung disorders that affects the parenchyma and is often associated with inflammation and/or fibrosis. Clinically, there is a great need for biomarker development for these disorders, to help diagnosis, treatment selection and assessment of efficacy as well as to predict progression. Thus far, no broadly validated biomarker exists for ILD, due to the existence of a very large number of disorders of often-unknown etiology, overlapping symptoms and disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…20 With the understanding of the basic cellular processes responsible for pulmonary fibrosis, numerous molecular biomarkers associated with disease progression have been identified, but clinical trials have yet to validate the clinical efficacy of these markers. 1 Research has revealed that OPN is highly expressed in lung diseases, and directly or indirectly involved in the regulation of granuloma formation and fibrosis. 21 In an experimental study on mice it was found that after exposure to titanium dioxide, mice not only develop a fibroproliferative lung disease, but also showed increased expression of OPN mRNA; and in turn increased levels of OPN in bronchoalveolar lavage fluid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 With the understanding of the basic cellular processes responsible for pulmonary fibrosis, numerous molecular biomarkers associated with disease progression have been identified, but clinical trials have yet to validate the clinical efficacy of these markers. 1 Research has revealed that OPN is highly expressed in lung diseases, and directly or indirectly involved in the regulation of granuloma formation and fibrosis. 21 In an experimental study on mice it was found that after exposure to titanium dioxide, mice not only develop a fibroproliferative lung disease, but also showed increased expression of OPN mRNA; and in turn increased levels of OPN in bronchoalveolar lavage fluid.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of which, there is extensive tissue destruction leading to altered lung function; such as, restricted ventilation, hypoxemia, shortness of breath, exercise limitation and ultimately death from respiratory failure. 1,2 A large number of diffuse parenchymal lung disorders are grouped together as ILD, because of their common clinical, radiological and histopathological features. 3 ILD is composed of more than 200 recognized entities, classified into subtypes depending on their cause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation